1988
DOI: 10.1016/0304-3959(88)90179-0
|View full text |Cite
|
Sign up to set email alerts
|

Cluster headache pain vs. other vascular headache pain: differences revealed with two approaches to the McGill Pain Questionnaire

Abstract: We compared cluster headache pain and other vascular (migraine and mixed) headache pain on pain intensity ratings and the McGill Pain Questionnaire (MPQ). Cluster headache sufferers reported not only more intense pain and more affective distress, but also different pain qualities than did migraine and mixed headache sufferers. The pain qualities that best distinguished cluster headaches from other vascular headaches were the presence of punctate pressure and thermal sensations and the absence of dull pain. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…In previous research, a low usage of most of the affective word subclasses of the MPQ, demonstrating a relatively lower affective component, was found in pain after tooth extraction and in tooth pain 15 , 19 , 28 . On the contrary, the affective dimension of pain was found to be high in patients with cluster headache compared to patients with migraine or mixed headache, 21 in chronic pain compared to acute pain, 29 and in myogenous facial pain and in facial pain as a somatoform disorder compared to pain of the TMJ 24,25 . Our present data seem to confirm that high levels of the affective dimension prevail in some types of pain, independently of the level of pain.…”
Section: Commentsmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous research, a low usage of most of the affective word subclasses of the MPQ, demonstrating a relatively lower affective component, was found in pain after tooth extraction and in tooth pain 15 , 19 , 28 . On the contrary, the affective dimension of pain was found to be high in patients with cluster headache compared to patients with migraine or mixed headache, 21 in chronic pain compared to acute pain, 29 and in myogenous facial pain and in facial pain as a somatoform disorder compared to pain of the TMJ 24,25 . Our present data seem to confirm that high levels of the affective dimension prevail in some types of pain, independently of the level of pain.…”
Section: Commentsmentioning
confidence: 85%
“…It has been found that the MPQ satisfactorily discriminates between reversible and irreversible tooth nerve damage, 19 trigeminal neuralgia and atypical facial pain, 20 cluster headache and migraine, 21 and between various types of facial pain 22,23 . More recently, the MPQ consistently discriminated between craniomandibular joint pain and facial pain as a somatoform disorder, 24 and between temporomandibular joint (TMJ) pain and myogenic facial pain 25 …”
mentioning
confidence: 99%
“…Descriptite data on this sample are also shown in Table 1. Disease severity was assessed by a question asking patients to rate their current disease activity on a 4-point scale from 1 (not active) to 4 (very active).…”
Section: Studymentioning
confidence: 99%
“…Specific verbal descriptors of the MPQ have also been shown to discriminate between reversible and irreversible damage of the nerve fibers in a tooth,S and between leg pain caused by diabetic neuropathy and leg pain arising from other cause. 13 Jerome et al 9 further showed that the MPQ discriminates between cluster headache pain and other vascular (migraine and mixed) headache pain. It is clear that there are appreciable and quantifiable differences in the way various types of pain are described, and that .patients with the same disease or pain syndrome tend to use remarkably similar words to communicate what they feel.…”
Section: The Mcgill Pain Questionnaire (Mpq) and The Language Of Painmentioning
confidence: 99%